Strategi Meningkatkan Kemampuan Bahasa Inggris Mahasiswa STMIK STIKOM Indonesia Melalui Pemanfaatan Video Online Youtube - I Kadek Agus Bisena; Ni Nyoman Ayu J. Sastaparamitha (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2021)
The current generation that is known as the millennium generation is synonymous with technological and educational developments. This phenomenon is a strategy that can be used by advocates of foreign languages, especially English in packaging a material to be taught. One of the choices is the use of youtube online videos as supporting teaching materials. The technology is very easy to access, especially STMIK STIKOM Indonesia students, where almost all students have the youtube application. This study uses a qualitative description analysis method to see how attractive YouTube videos are among students, as well as video criteria that are considered interesting by them. The results of the study are packaging of youtube online videos that are tailored to the teaching material delivered to STMIK STIKOM Indonesia students, as the lecturers' handlers and student references in their own creative learning.